Transpormasi Ramah Pelajar Dan Dampaknya Terhadap Karakter Di Siplin Dalam Pembelajaran Pendidikan Agama Islam - Samsul Hadi; Riky Supratama (Ar-Ruhul Ilmi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study explores how student-friendly transformation within Islamic Religious Education (PAI) classrooms reshapes the learning atmosphere into one that feels more humane, warm, and deeply meaningful for students. Amid the rapid shifts within contemporary education, the demand for teaching approaches that are empathetic and responsive to learners’ emotional and psychological needs continues to grow. Using a qualitative approach with a case study design, the research gathered data from PAI teachers, students, and school administrators through detailed observations, in-depth interviews, and documentation. The analysis, guided by the Miles and Huberman framework, allowed each finding to be examined systematically and reflectively. The results reveal that student-friendly practices do more than simply create a pleasant classroom environment—they cultivate spaces of genuine dialogue, mutual respect, and emotional safety. Such an atmosphere encourages students to participate more actively, internalize classroom rules with understanding, and develop self-driven discipline rather than obedience based on fear or external pressure. These findings highlight that humane pedagogical practices closely align with the Islamic values of compassion, etiquette, and wisdom. Consequently, this study offers meaningful contributions to contemporary Islamic pedagogy by presenting an instructional model that is more relevant to today’s learners and more transformative in shaping their character.